Gloves, Veils and Scenes With ”Mighty Arms”: Echoes of War and Revolution in the Fictions by Virginia Woolf and Jelena Dimitrijević (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This comparison of a short story by Virginia Woolf, ”Mrs. Dalloway in Bond Street”, and Letters from Salonica as well as the novel Nove by Jelena Dimitrijević, points to the extent in which the great turmoils such as World War One, or some other wars and revolutions of the time, permeate the works written about the seemingly private and secluded lives of women. The same perspective is used for comparative analysis of the British and the Balkan modernistic representations of masculinity. The paper aims not only at making connections between these two parts of Europe, but also at questioning the range of the notion of modernism, which should, as it is argued, include the women's writings written in or about the Balkans.
Keywords: World War One; women's writing; masculitinities; modernism; Balkans